First COVID-19 case in Zambia — Comparative phylogenomic analyses of SARS-CoV-2 detected in African countries. (January 2021) - Simulundu, Edgar; Mupeta, Francis; Chanda-Kapata, Pascalina; Saasa, Ngonda; Changula, Katendi; Muleya, Walter; Chitanga, Simbarashe; Mwanza, Miniva; Simusika, Paul; Chambaro, Herman; Mubemba, Benjamin; Kajihara, Masahiro; et al.
Highlights: While African countries were relatively spared initially, when COVID-19 was first reported from China, the frequent travel links between China, Europe and Africa, meant importation of SARS-CoV-2 into Africa was inevitable. In preparation, Zambia had applied a multisectoral national epidemic disease surveillance and response system resulting in the identification of the first case within 48 h of the individual entering the country by air travel from a trip to France. Phylogenomic analysis showed that the detected SARS-CoV-2 belonged to lineage B.1.1., sharing the last common ancestor with SARS-CoV-2 strains recovered from South Africa. At the African continental level, our analysis showed that B.1 and B.1.1 lineages appear to be predominant in Africa. Whole genome sequence analysis should be part of all surveillance activities to monitor the origin and evolution of SARS-CoV-2 lineages across Africa. Abstract: Since its first discovery in December 2019 in Wuhan, China, COVID-19, caused by the novel coronavirus SARS-CoV-2, has spread rapidly worldwide. While African countries were relatively spared initially, the initial low incidence of COVID-19 cases was not sustained for long due to continuing travel links between China, Europe and Africa. In preparation, Zambia had applied a multisectoral national epidemic disease surveillance and response system resulting in the identification of the first case within 48 h of the individual entering the country by air travel from a trip to France. Contact tracing showed that SARS-CoV-2 infection was contained within the patient's household, with no further spread to attending health care workers or community members. Phylogenomic analysis of the patient's SARS-CoV-2 strain showed that it belonged to lineage B.1.1., sharing the last common ancestor with SARS-CoV-2 strains recovered from South Africa. At the African continental level, our analysis showed that B.1 and B.1.1 lineages appear to be predominant in Africa. Whole genome sequence analysis should be part of all surveillance and case detection activities in order to monitor the origin and evolution of SARS-CoV-2 lineages across Africa.